The p-ring Trench Schottky IGBT: A solution towards latch-up immunity and an enhanced safe-operating area - Antoniou, Marina; Udrea, Florin; Lophitis, Neophytos; Corvasce, Chiara; De-Michielis, Luca (My University, 2020)
A novel Trench IGBT design, namely the p-ring Trench Schottky IGBT, with improved latch-up immunity and an enhanced safe-operating area is proposed. This design improves the performance of the FS+ IGBT by facilitating the collection of holes through a p-doped (p-ring) buried region connected through a Schottky contact to the source/cathode contact. This unique structure approach allows the improvement in the device reliability and it is shown under numerical studies to be highly effective in expanding the safe operating area (SOA), suppress dynamic avalanche, improve the latch up robustness and have the potential to improve the device switching operation.
Keywords: JBS; Junction Barrier Schottky diodes; MPS; SiC; SiC diodes; surge current